Factors influencing the prescribing behaviour of independent prescriber optometrists: a qualitative study using the Theoretical Domains Framework. (20th February 2021) - Spillane, Daniel; Courtenay, Molly; Chater, Angel; Family, Hannah; Whitaker, Angela; Acton, Jennifer H
Abstract: Purpose: Whilst the number of independent prescriber (IP) optometrists in the United Kingdom is increasing, there is limited evidence describing the experiences of these individuals. The Theoretical Domains Framework (TDF) provides an evidence‐based approach to understand determinants of behaviour. This conceptual framework can enable mapping to the COM‐B behaviour change model and the wider Behaviour Change Wheel to develop interventions to optimise behaviour‐change and healthcare processes more systematically. The study aimed to use the TDF to identify the factors that influence independent prescribing behaviour, and to map these findings to the COM‐B system to elucidate the relevant intervention functions, in order to identify the support required by optometrist prescribers. Methods: Using a qualitative design, semi‐structured interviews based on the TDF were undertaken with independent prescriber optometrists. Thematic analysis was used to identify themes inductively, which were then deductively mapped to the TDF and linked to the COM‐B. Results: Sixteen participants (9 male, 7 female; median age 45 years, range 28–65 years), based in community ( n = 10) and hospital ( n = 6) settings, were interviewed. Eleven of the TDF domains were found to influence prescribing behaviour. Findings highlighted the need for good communication with patients (TDF domain: Skills, COM‐B: Capability); confidence (TDF domain: Beliefs about capabilities, COM‐B: Motivation); good networks and relationships with other healthcare professionals, e.g., general practitioners (TDF domain: Social influences, COM‐B: Opportunity; TDF domain: Social/professional role and identity, COM‐B: Motivation); the need for appropriate structure for remuneration (TDF domain: Reinforcement, COM‐B: Motivation; TDF domain: Social/professional role and identity, COM‐B: Motivation) and the provision of professional guidelines (TDF domain: Knowledge, COM‐B: Capability; TDF domain: Environmental context and resources, COM‐B Opportunity). Conclusions: Having identified theory‐derived influencers on prescribing decisions by optometrists, the findings can be used to develop a structured intervention, such as a support package to help optimise prescribing by optometrists, with the ultimate goal of eye care quality improvement.